Onstage violence in sixteenth-century French tragedy - Meere, Michael (Oxford University Press, 2021)
This volume studies the representation of violence in tragedies written for the French stage during the sixteenth century, and explores its connection with issues such as politics, religion, gender, and militantism to place the plays within their historical, cultural, and theatrical contexts. The performance of violence on the stage has played an integral role in French tragedy since its inception. Onstage Violence in Sixteenth-Century French Tragedy is the first book to tell this story. It traces and examines the ethical and poetic stakes of violence, as playwrights were experimenting with the newly discovered genre during decades of religious and civil war (c. 1550-1598). 0The study begins with an overview of the origins of French vernacular tragedy and the complex relationships between violence, performance, ethics, and poetics. The volume focuses on specific plays and analyzes biblical, mythological, historical, and politically topical tragedies-including the stories of Cain and Abel, David and Goliath, Medea, the Sultan Suleyman the Magnificent, the Roman general Regulus, and the assassination of the Duke of Guise in 1588-to show how the multifarious uses of violence on stage shed light on a range of pressing issues during that turbulent time, such as religion, gender, politics, and militantism
10.1093/oso/9780192844132.001.0001
Keywords: French drama (Tragedy); Violence in literature; Violence in the theater; French drama; Literary criticism; Criticism; interpretation; etc